2009
DOI: 10.1523/jneurosci.2660-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Tripartite Purinergic Modulation of Central Respiratory Networks during Perinatal Development: The Influence of ATP, Ectonucleotidases, and ATP Metabolites

Abstract: ATP released during hypoxia from the ventrolateral medulla activates purinergic receptors (P2Rs) to attenuate the secondary hypoxic depression of breathing by a mechanism that likely involves a P2Y 1 R-mediated excitation of preBötzinger complex (preBötC) inspiratory rhythm-generating networks. In this study, we used rhythmically active in vitro preparations from embryonic and postnatal rats and ATP microinjection into the rostral ventral respiratory group (rVRG)/preBötC to reveal that these networks are sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 70 publications
7
72
0
Order By: Relevance
“…Local application of the P2Y 1 agonists 2-methylthio-ADP and (N)-methanocarba-2-methylthio-ADP (MRS2365) to neurons in the XII nucleus evoked a tonic discharge, although UTP also had an effect (de Souza Alvares et al, 2007), perhaps indicating involvement also of P2Y 2 receptors. Further experiments led to the conclusion that ATP is a potent excitatory modulator of the inspiratory network with a dynamic interaction between the actions of ATP at P2 receptors and ectonucleotidases that degrade it to metabolites that act on P2Y and P1 receptors (Huxtable et al, 2009). Connexin hemichannel-mediated CO 2 -dependent release of ATP in the medulla oblongata contributes to central respiratory chemosensitivity (Huckstepp et al, 2010).…”
Section: Central Control Of Respirationmentioning
confidence: 99%
“…Local application of the P2Y 1 agonists 2-methylthio-ADP and (N)-methanocarba-2-methylthio-ADP (MRS2365) to neurons in the XII nucleus evoked a tonic discharge, although UTP also had an effect (de Souza Alvares et al, 2007), perhaps indicating involvement also of P2Y 2 receptors. Further experiments led to the conclusion that ATP is a potent excitatory modulator of the inspiratory network with a dynamic interaction between the actions of ATP at P2 receptors and ectonucleotidases that degrade it to metabolites that act on P2Y and P1 receptors (Huxtable et al, 2009). Connexin hemichannel-mediated CO 2 -dependent release of ATP in the medulla oblongata contributes to central respiratory chemosensitivity (Huckstepp et al, 2010).…”
Section: Central Control Of Respirationmentioning
confidence: 99%
“…This is supported by our demonstration with ATP biosensors, where to obtain concentrations of 10 M ATP below the slice surface, the bath concentration must be raised 100-fold to 1 mM . Also, ATP diffuses small distances in tissue due to an active process that we attribute to enzymatic breakdown (Huxtable et al, 2009). Second, with bath application, drug concentration rises slowly and can lead to receptor desensitization/internalization, which will greatly attenuate responses.…”
Section: Ca 2ϩ Imaging Of Prebötc Cells In Rhythmic Medullary Slicesmentioning
confidence: 99%
“…The vast majority of inspiratory neurons also respond to ATP with inward currents under whole-cell recording conditions . Neurons in this region would therefore be expected to respond to ATP; however, there is greater potential for ATP hydrolysis by ectonucleotidases with bath application Huxtable et al, 2009) (i.e., ATP has to diffuse through tissue, whereas with local application, it is injected into the site of interest) and for receptor desensitization/internalization (as the ATP concentration gradually increases). In addition to enzymatic breakdown and receptor desensitization, the lack of a neuronal calcium increase to bath-applied ATP can also be attributed to the fact that we are only measuring changes in intracellular calcium.…”
Section: Atp Sensitivity Of Prebötc Gliamentioning
confidence: 99%
“…The prevalence of these signalling pathways has led to the hypothesis that the effects of adenosine at its receptors are secondary to the effects of nucleotides at P2 receptors [9][10][11] . Depending on the receptor subtype expressed, ATP enhances or inhibits glutamate neurotransmission [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the receptor subtype expressed, ATP enhances or inhibits glutamate neurotransmission [12] . Thus, it has been demonstrated that ATP can produce inhibitory or excitatory effects, via P2X or P2Y receptors, with subsequent inhibitory effects via A 1 receptors or excitatory effects via A 2A receptors after metabolism to adenosine [10,11] .…”
Section: Introductionmentioning
confidence: 99%